2018
DOI: 10.4102/phcfm.v10i1.1807
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of school health nurses regarding the provision of the school health service delivery in the Tshwane district

Abstract: BackgroundIrrespective of the provision of an integrated school health policy, the school health nurses continue to experience multiple challenges regarding the provisioning of school health service delivery.AimThe aim of this paper was to explore and describe the experiences of school health nurses regarding school health service delivery in the Tshwane district.SettingSchools in the Tshwane district in Pretoria were used in the study.MethodsA qualitative and descriptive phenomenological design was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
2
13
0
4
Order By: Relevance
“…The National learner educator ratio was estimated at 30.9:1 in 2016 (Department of Basic Education, 2018). The high learner to educator ratio and the substantial number of schools also contribute to the difficulty in efficiently running school-based health programs (Dibakwane & Peu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The National learner educator ratio was estimated at 30.9:1 in 2016 (Department of Basic Education, 2018). The high learner to educator ratio and the substantial number of schools also contribute to the difficulty in efficiently running school-based health programs (Dibakwane & Peu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations from a study by Dibakwane and Peu (2018) concurred with these findings. They suggested that the government should employ new nurses or those who have retired as additional human resources.…”
Section: Ministry Of Health Should Recruit School Health Nursesmentioning
confidence: 57%
“…The implementation of similar policies [17] that rely on collaborations between the DoH and DoE has proven somewhat challenging. [18][19][20] Therefore, the success of…”
Section: Discussionmentioning
confidence: 99%